La Scuola romana e la Rinascita tomistica: principî metafisici e metodo teologico - Vergano, Giancarlo (Alpha Omega, 2020)
Summary: The unique feature of this third specification of methodology lies in its careful consideration of the nature of theology; this is, in fact, an organic science within a system complete in itself. In theology, the truths which are examined as it proceeds are united between themselves by the unity of the composite system of this field of knowledge. The requirements and the rules of this science depend upon the clear principles of metaphysics which, in its turn, the revival of Thomism has brought into the light of day. Key words: Thomistic revival, theological methodology, positive data, the notions of act, accident and analogy. Parole chiave: rinascita tomistica, metodologia teologica, dato positivo, nozione di atto, accidente, analogia. <iframe class="ginger-extension-definitionpopup" style="left: 8px; top: 111px; z-index: 2147483646; display: none;" src="chrome-extension://kdfieneakcjfaiglcfcgkidlkmlijjnh/content/popups/definitionPopup/index.html?title=Key&description=metal%20device%20shaped%20in%20such%20a%20way%20that%20when%20it%20is%20inserted%20into%20the%20appropriate%20lock%20the%20lock's%20mechanism%20can%20be%20rotated">